Weighing the evidence on the relation between external corporate financing activities, accruals and stock returns - Cohen, Daniel A.; Lys, Thomas Z. (Journal of Accounting and Economics, 2006)
Bradshaw, Richardson, and Sloan (BRS) find a negative relation between their comprehensive measure of corporate financing activities and future stock returns and future profitability. Noticing that accounting accruals are increases in net operating assets on a company's balance sheet, we question whether it is possible to distinguish between the ‘external financing anomaly’ documented by BRS and the ‘accrual anomaly’ first documented by Sloan [1996. Do stock prices fully reflect information in accruals and cash flows about future earnings? The Accounting Review 71, 289–315]. We show that once controlling for total accruals, the relation between external financing activities and future stock returns is attenuated and not statistically significant. These findings are consistent with Richardson and Sloan [2003. External financing, capital investment and future stock returns. Working Paper, University of Pennsylvania and University of Michigan].